Carbon nanotubes biosensors for high throughput electrophysiological measurement in living cells. - Wellym. (2009)
Carbon NanoTubes (CNTs) is probably the most revolutionary discovery in nanotechnology nowadays. CNT is known for its unique mechanical, electrical, and thermal properties. This has lead CNT as a hot topic to research on as it promises many applications that conventional material will not do. This report especially discusses the development of Carbon NanoTube Field Effect Transistor (CNTFET) for analysis of cell’s electrophysiology. We employ a dense array of SWCNT network work as a sensor mean. This model is easy to fabricated, simple, and capable of mass production. We start our report by briefly presenting the theory, properties, and applications behind CNT. We also discuss some basic required knowledge about CNTFET and cell’s electrophysiology. In our experiment, we firstly discuss the exponential relationship between different concentrations of SWCNT applied to build CNTFET devices using drop casting method. We also show the common characteristic of our device. Next discussion is to observe Smooth Muscle Cells (SMCs) growth on CNT-Network. We do an experiment to extract signal from SMC by application of stimulus and under high [K+] solution. We also measure the significance of Carbamoylcholine and quinidine on the HL-1 heart cells under fibronectin coating CNT-FET device where we find significance changes in frequency of the produced spikes. Intracellular measurement (pipette recording) agrees with our CNTFET measurement. In last section, we provide some recommendations to ways overcome some problems with our experiments.